THE ABUNDANCES OF HEAVY ELEMENTS IN RED SUPERGIANTS OF MAGELLANIC CLOUDS - Gopka, V.; Yushchenko, A; Kovtyukh, V.; Shavrina, A.; Yushchenko, V.; Vasilyeva, S.; Pavlenko, Y.; Andrievsky, S. (Одеські астрономічні публікації, 2013)
The spectra of Magellanic Clouds (MC) supergiants PMMR23, PMMR144 and RM 1-667 with resolving power R=30,000 and signal to noise ratio near 100 obtained at3.6 metertelescope in Chile were analysed. We present are port on the detailed investigation of MC supergiants, with special attention to the thorium abundance in these stars. The abundance patterns of three supergiants show that r-process elements are clearly detected in the atmospheres of investigated stars, but the bundances of s-processes elements can vary from star to star.